2007
DOI: 10.1037/0022-3514.93.5.880
|View full text |Cite
|
Sign up to set email alerts
|

Between facets and domains: 10 aspects of the Big Five.

Abstract: Factor analyses of 75 facet scales from 2 major Big Five inventories, in the Eugene-Springfield community sample (N=481), produced a 2-factor solution for the 15 facets in each domain. These findings indicate the existence of 2 distinct (but correlated) aspects within each of the Big Five, representing an intermediate level of personality structure between facets and domains. The authors characterized these factors in detail at the item level by correlating factor scores with the International Personality Item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

56
1,719
8
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,567 publications
(1,799 citation statements)
references
References 65 publications
56
1,719
8
16
Order By: Relevance
“…In contrast, Time Management Behaviour represents a selfregulatory behaviour, the means by which students arrange their work in the most efficient way. In support of this finding, we found that TMB was best accounted for by Industriousness (C) and Orderliness (C), traits by which individuals prefer to pursue their goals actively and keep their goals well organised as they do so (DeYoung et al, 2007).According to cybernetic theory, traits provide the controls to direct self-regulatory processes in pursuit of goals. The study reported above provides some evidence that students higher in Conscientiousness and Openness/Intellect in particular, might be more effective at initiating the self-regulatory strategies that confer the possibility of better achievement at university.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…In contrast, Time Management Behaviour represents a selfregulatory behaviour, the means by which students arrange their work in the most efficient way. In support of this finding, we found that TMB was best accounted for by Industriousness (C) and Orderliness (C), traits by which individuals prefer to pursue their goals actively and keep their goals well organised as they do so (DeYoung et al, 2007).According to cybernetic theory, traits provide the controls to direct self-regulatory processes in pursuit of goals. The study reported above provides some evidence that students higher in Conscientiousness and Openness/Intellect in particular, might be more effective at initiating the self-regulatory strategies that confer the possibility of better achievement at university.…”
supporting
confidence: 64%
“…Woods and Sofat (2013) examined the aspects of Extraversion in their study and found that Assertiveness was significantly and positively associated with work engagement. While Assertiveness indicates a personality that takes charge and is quick to act, Enthusiasm describes an individual who enjoys having fun with lots of people (DeYoung et al, 2007). This suggests that work engagement is more likely to be related to Assertiveness than Enthusiasm.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Agreeableness is a broad dimension of personality that reflects a wide range of cooperative and affiliative behaviors; in the NEO-PI-R representation of personality, for example, Agreeableness comprises 6 narrower 'facets' that some researchers conceptualize as distinct aspects of Politeness and Compassion (DeYoung et al, 2007). We hypothesized that the trait and trait-by-situation effects we observed were likely to be driven primarily by the facets related to compassion for other people (Trust, Altruism, and TenderMindedness) rather than the facets associated with acquiescence and politeness (Straightforwardness, Compliance, and Modesty).…”
Section: Facet-level Analysis Of Agreeablenessmentioning
confidence: 99%